Tradisi Panyambleh Kucit Butuan Dalam Upacara Macaru Sasih Kelima Di Ulun Setra Desa Pakraman Batuyang Kecamatan Sukawati Kabupaten Gianyar - Ni Kadek Yuli Anggriani (Jurnal Penelitian Agama Hindu, 2019)
The Panca Yadnya ceremony is inseparable from the life of the Hindu community in Bali. Like the Panyambleh Kucit Butuan tradition carried out by the people in Pakraman Batuyang village which is one of the series of Panca Yad namely Bhuta Yad which is held once a year precisely falls on the day of the fifth Tilem Sasih held in Ulun Setra by giving Pacaruan with Kucit Butuan. The song by Kucit Butuan in Ulun Setra, all of the Sesuhunan in the form of Barong, Rangda and Bhatara-bhatari Kahyangan Tiga participated in the implementation of the tradition of Panyambleh Kucit Butuan. The results obtained in this study: 1) The procession of the Panyambleh Kucit Butuan tradition in Ulun Setra, Pakraman Batu Village which includes several series, namely Nedunan Ida Bhatara Ratu Sakti. After that, Ida Bhatara Barong and Rangda went hand in hand towards the location of the traditional retreat, namely to Ulun Setra, Pakraman Batuyang Village (worship to teben) which was carried out in the fifth tilem. Arriving at the place of execution The tradition of chanting (worshiping the teben) is carried out with a renewal ceremony ready for brumbum by giving a cucumber dish but previously held the tabuh as a series of rituals in the traditional tradition with this point, the tool or means of the Tradition by Kucit Butuan, covering Pejati Upa witness, segehan agung, caru is ready for brumbun, Banten which is used in the Chinese tradition with a hint of worship Hulu and teben consists of several parts, among others, male black Butuan Cucumber, Mantai Panyambleh Kucit Butuan Tradition, which is the Baruna Astawa. Baruna Astawa is the main instrument used to carry out the traditional tradition of chanting, with a hint of a point, Dhurga Astawa. Astawa Dhurga is the main pillar used for ngastawa in the implementation of the novel ceremony ready for brumbun and panyamblehan kucit butuan in a series of cucumber grains, Manggala The tradition of purified grains covering the Pinandita / Pamangku Pura Penataran Agung and Pemangku Manca Desa Khayangan.2) Panyambleh Kucit Butuan's traditional function in Ulun Setra, Pakraman Batu Village, which is a traditional tradition with a lot of functions for the people of Pakraman Batuyang Village in general as a form of community service to the Creator of effort. 3) The impact of the Panyambleh Kucit Butuan tradition in Ulun Setra Pakraman Village consists of positive and negative impacts.